Intensifiers in late Modern English a sociopragmatic approach to courtroom discourse - Claridge, Claudia 1965- (Cambridge University Press, 2024)
The development of intensifiers has long been identified as an area of vibrant change in Late Modern English. This groundbreaking book provides the first comprehensive study of intensifiers in this period, and shows how they have changed over time. It uses speech-based and interactive data from the Old Bailey courthouse in London, enriched by extralinguistic information in the Old Bailey Corpus, to investigate an unprecedented range of intensifiers, including downtoners, boosters, and maximizers. The courtroom acts as a social microcosm of the period, providing unique insights on gender, class, and courtroom roles, and their effects on language use. The usage of intensifiers is illuminated from a lexico-grammatical angle, focusing on their formal and semantic features, as well as those of the items they modify. These perspectives are linked to temporal developments from 1720 to 1913, to offer a complete picture of variation and change in the intensifier area
Title from publisher's bibliographic system (viewed on 15 Mar 2024)
Keywords: English language -- Intensification; Law -- Language